2019
DOI: 10.1182/blood-2019-127120
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole Prophylaxis during Early Phases of Allogeneic HSC Transplantation Is Not Associated to an Increase Need of Cyclosporin-a Dose Modification

Abstract: Background: Isavuconazole is an effective treatment of invasive fungal infections (IFI). Since its broad spectrum of activity and favorable toxicity, it could also be used as a prophylaxis. Experience in use of isavuconazole as prophylaxis of IFI is, however, limited. In allogeneic transplant setting, its feasibility should also be assessed in regard of changes of Cyclosporine (CYA) metabolism. Aim: To evaluate feasibility of the administration of Isavuconazole as short term prophylaxis during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…18 A prospective study in 34 HSCT patients found there is no difference between ISA and FLC and their effect on CSA levels or average number of CSA dose adjustments. 19 Patients in the ISA group needed on average 1.3 dose adjustments, but the specific dose adjustments were not quantified. As the newest azole, ISA is the least studied among the azole antifungals and there are limited published studies in regards to its effects on CNI doses.…”
Section: Discussionmentioning
confidence: 99%
“…18 A prospective study in 34 HSCT patients found there is no difference between ISA and FLC and their effect on CSA levels or average number of CSA dose adjustments. 19 Patients in the ISA group needed on average 1.3 dose adjustments, but the specific dose adjustments were not quantified. As the newest azole, ISA is the least studied among the azole antifungals and there are limited published studies in regards to its effects on CNI doses.…”
Section: Discussionmentioning
confidence: 99%